2014
DOI: 10.1007/s12640-014-9494-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Attenuation of Protein Disulfide Isomerase Activity Through S-Mercuration and Neurotoxicity Induced by Methylmercury

Abstract: Methylmercury (MeHg), an environmental pollutant, causes neuronal death via endoplasmic reticulum (ER) stress; however, the precise mechanism is not fully understood. The aim of this study was to elucidate the possible mechanism of MeHg-induced neurotoxicity. Treatment with MeHg resulted in a loss of cell viability in a concentration-dependent manner accompanying the expression of ER stress marker genes in human neuroblastoma SH-SY5Y cells. We next attempted to identify a target protein for MeHg in the ER. MeH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…A subsequent study showed that pretreatment with Trolox significantly blocked MeHg-induced ER stress, unfolded protein response activation, and apoptosis in neuronal cells [ 71 ], confirming that MeHg-mediated oxidative stress causes ER stress and apoptosis. In contrast, it has been reported that MeHg directly causes ER stress through interaction with protein disulfide isomerase (PDI) [ 18 ]. PDI localizes in the ER and catalyzes all of the reactions involved in native disulfide bond formation in the ER [ 82 ].…”
Section: Cellular Stress Pathways Triggered By Mehg-mediated Oxidamentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent study showed that pretreatment with Trolox significantly blocked MeHg-induced ER stress, unfolded protein response activation, and apoptosis in neuronal cells [ 71 ], confirming that MeHg-mediated oxidative stress causes ER stress and apoptosis. In contrast, it has been reported that MeHg directly causes ER stress through interaction with protein disulfide isomerase (PDI) [ 18 ]. PDI localizes in the ER and catalyzes all of the reactions involved in native disulfide bond formation in the ER [ 82 ].…”
Section: Cellular Stress Pathways Triggered By Mehg-mediated Oxidamentioning
confidence: 99%
“…It has been demonstrated that the dysfunction of PDI enzymatic activity by the oxidative modification of active cysteine by nitric oxide (NO) induced by treatment with N-Methyl-D-aspartate causes the accumulation of newly synthesized unfolded protein in the ER lumen, resulting ER stress [ 86 ]. Similar to NO, the MeHg-modified C-terminal catalytic domain in PDI was detected using matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF/MS) analysis, suggesting that PDI is a target protein for MeHg in the ER [ 18 ]. In addition, treatment with MeHg significantly attenuated the enzymatic activity of PDI.…”
Section: Cellular Stress Pathways Triggered By Mehg-mediated Oxidamentioning
confidence: 99%
See 1 more Smart Citation
“…Like the two active TrpCysGly-HisCysLys sites of PDI, Cys residues that are adjacent to a basic environment (i.e., Lys, Arg, or His) have low pKa values and are targeted for covalent modification. In the ER, S-nitrosylation, S-glutathionylation, and S-mercuration occur on the active sites of PDI, inhibiting its enzymatic activity and promoting the unfolded protein response and ER stress 15,52,53 . Uehara et al reported that PDI is S-nitrosylated in brain tissues from patients with Parkinson's and Alzheimer's diseases and that S-nitrosylation impairs the protective effect of PDI on neurotoxicity that is induced by protein misfolding in neurodegenerative disorders 15 .…”
Section: Regulators Of Extracellular Pdi Activitymentioning
confidence: 99%
“…7,8) S-Nitrosylation and -mercuration of PDI in active sites promote endoplasmic reticulum (ER) stress and unfolded protein response (UPR). We earlier demonstrated that inositol-requiring enzyme 1α (IRE1α), a sensor of ER stress that is located within the ER membrane, is also directly modified and regulated by NO.…”
mentioning
confidence: 99%